2020
DOI: 10.1097/md.0000000000022443
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between calcifications and structural lesions on hand radiography and axial calcifications on CT-scan

Abstract: The objectives of this study were to describe the prevalence and characteristics of radiographic lesions of the hands, and calcifications of the spine on computer tomography scans (CT-scans), and to investigate the relationships between radiographic and CT-scan abnormalities and clinical features in a population of patients with systemic sclerosis (SSc). Subjects underwent X-ray examination of the hands, and thoracic or thoraco-abdominal and pelvic CT scan or lumbar CT scan in the year. Structural l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…When assessing SSc ILD prevalence, we observed a wide range (26.1% to 88.1%) 37 44 in reported estimates, but when studies were dichotomised into single-centre studies and multicentre studies, it became clear that the highest variability was contributed by single centre studies (SSc prevalence, 31.2%–88.1%). 43–46 Owing to a smaller number of studies reporting incidence, we were unable to observe whether the same challenge existed.…”
Section: Discussionmentioning
confidence: 96%
“…When assessing SSc ILD prevalence, we observed a wide range (26.1% to 88.1%) 37 44 in reported estimates, but when studies were dichotomised into single-centre studies and multicentre studies, it became clear that the highest variability was contributed by single centre studies (SSc prevalence, 31.2%–88.1%). 43–46 Owing to a smaller number of studies reporting incidence, we were unable to observe whether the same challenge existed.…”
Section: Discussionmentioning
confidence: 96%
“…Univariate analysis revealed that calcinosis patients exhibited a higher proportion of severe organ involvement, particularly in vascular and GI disease. Other clinical features did not significantly correlate with the calcinosis subset in SSc, although recent research suggests a positive link between subcutaneous calcinosis at disease onset and the presence of pulmonary arterial hypertension [ 42 ]. SSc patients had a higher frequency of DU history, which aligns with the proposal of a link between calcinosis and vasculopathy by Avouac et al, as their patient population with calcinosis was more likely to have a history of DU [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unusual locations like the spine or face are reported in some studies [15][16][17][18]20]. Spinal calcinosis, which was found to occur commonly in association with acral calcinosis [21], can lead to radiculopathy, spinal stenosis, or cord compression [15][16][17][18]21,22].…”
Section: Location and Its Impactmentioning
confidence: 99%